PENERAPAN DATA MINING METODE APRIORI TERHADAP DATA PENJUALAN PADA PT TASINDO TOTAL INPRODUCTS - Laurence; Sasa Ani Arnomo (Computer Science and Industrial Engineering, 2022)
Bags are one of the products that are in great demand by buyers from various circles. The sale of bags is one of the businesses with great opportunities due to its wide range, ranging from women and men of all ages, as well as various types that can be used in all activities. The a priori algorithm is a type of association rule in data mining. Apriori is a very well-known algorithm for finding high-frequency patterns. High-frequency patterns are patterns of items in a database that have a frequency or support above a certain threshold called the minimum support term. Using apriori algorithm can used to create marketing strategies